2020
DOI: 10.26848/rbgf.v13.3.p903-914
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coffee biochar on soil carbon, microbial biomass and enzymatic activities in Semiarid Entisol cultivated with maize

Abstract: The use of biochar can bring benefits such as long-term carbon sequestration and water use efficiency, being an alternative for semiarid regions. The objective of this study was to evaluate the impact of coffee biochar applied in sandy Entisol on maize growth, and soil chemical, microbial and biochemical attributes. The experimental design was completely randomized, distributed in a 2 x 4 + 1 factorial scheme, two types of wastes coffee ground (MCG) and coffee husks (MCH), four doses (4, 8, 12 and 16 Mg ha -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Biochar had no significant effect on microbial proportions, although BC10 and BC30 were significantly lower compared to BC0. According to Filho et al [ 106 ], the type, amount, and interaction of biochar has a significant impact on microbial biomass carbon. Since coffee biochar contains unstable organic carbon and has pores that can store large amounts of air and oxygen more quickly, which are crucial for the utilization and growth of microorganisms, its application to sandy soils increases the rate of microbial biomass growth and carbon content [ 107 ].…”
Section: Biochar Impactsmentioning
confidence: 99%
“…Biochar had no significant effect on microbial proportions, although BC10 and BC30 were significantly lower compared to BC0. According to Filho et al [ 106 ], the type, amount, and interaction of biochar has a significant impact on microbial biomass carbon. Since coffee biochar contains unstable organic carbon and has pores that can store large amounts of air and oxygen more quickly, which are crucial for the utilization and growth of microorganisms, its application to sandy soils increases the rate of microbial biomass growth and carbon content [ 107 ].…”
Section: Biochar Impactsmentioning
confidence: 99%
“…Recent studies suggest that the interaction of biochar in the soil can also influence the availability of P, due to changes in pH, in enzymatic efficiency, in the formation of organo-mineral complexes, which can increase the solubility of P through changes induced in the soil microbial community (Du et al, 2019;Li et al, 2020;Shi et al, 2020). Given these advantages for the physical, chemical, and biological properties of the soil (Butnan et al, 2015), biochar emerges as a promising and ecologically favorable alternative for enhancing yields of agricultural crops (Butnan et al, 2015;Martins Filho, 2020).…”
Section: Viability Of Biochar As a Component Of Microbial Inoculantsmentioning
confidence: 99%
“…Biochar can be employed in agriculture as fertilizers (Kamau et al 2019), mixed with mineral (NPK) fertilizers (Magalhães et al 2018), used as soil conditioners (Silva et al 2018), and employed as a substrate for growing plants (Dispenza et al 2016). Martins Filho et al (2020) and Silva et al (2021) also demonstrated the impact of coffee waste biochar on soil attributes, which provided an increase in nutrients and improved biological activity. Beyond these agricultural uses, important environmental applications have been shown for biochar, including increasing carbon stocks in soils, mitigating the greenhouse effect (Liu et al 2019), and remediating environments contaminated by heavy metals (Chwastowski et al 2020;Manzano et al 2020).…”
Section: Introductionmentioning
confidence: 99%